Employee Commitment and Organizational Performance in MKL Corporation: Basis for Action Plan - Asuten, Ivy Grace A.; Urbina, Marilou C.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigated the relationship between employee commitment and organizational performance in MKL Corporation with the goal of developing an action plan to improve company outcomes. The study was anchored on the premise that employee commitment plays a vital role in enhancing productivity, operational efficiency, and overall organizational success. A descriptive-correlational research design was employed, and data were collected from 47 respondents representing various departments within the company. The survey instrument measured three components of employee commitment—affective, continuance, and normative—as well as key indicators of organizational performance including productivity, efficiency, and employee retention. Results showed that the overall level of employee commitment was rated as high (mean = 3.20), with affective commitment scoring the highest. Organizational performance was perceived as generally positive (mean = 2.92), although efficiency received the lowest mean rating among the performance indicators. Pearson’s correlation coefficient revealed a moderate positive relationship (r = 0.58) between employee commitment and organizational performance, indicating that higher levels of employee commitment are associated with better organizational outcomes. Based on these findings, the study proposed a comprehensive action plan focused on four major areas: (1) enhancing employee engagement through meaningful activities and open communication; (2) offering career growth and training opportunities; (3) improving operational efficiency through process improvements; and (4) implementing retention strategies that address employee needs and motivations. These interventions aim to build a more dedicated and high-performing workforce, enabling MKL Corporation to maintain a competitive advantage and sustain long-term growth.